GOVERNMENT BUDGET IN SYSTEM OF COST RECOVERY ON INNOVATIONS PRODUCTION: VARIATIVE APPROACH - Elena A. MIDLER (Advanced Engineering Research, 2010)
Instruments of financing innovative processes in the aspect of cost refunding on innovations development are considered. Limits and possibilities of the state participation in the system priming reproduction of innovative products in the Russian economy are revealed. It is concluded that public and private mechanisms which local optimum is eliminated with cyclical swings parameters are complementary.